The Role Of Organizations In Forming The Character Of PAI UMSU Students - Dahlan, Alwi; Fadila Azmi, Ela; Aprillia, Widya (-, 2024)
This research aims to see how much influence student organizations have on the formation of the character of students at a university, especially at the Faculty of Islamic Religion (FAI). The method used by the author is a literature study where the sources are taken from various places, starting from news articles and several documents relating to the activities of student organizations. Then the data is analyzed using a descriptive method, namely a method that attempts to reveal results and statements whose sources have been obtained previously. The results of this research statement show that an organization has a fairly large role in shaping the character values of FAI students through student activities provided in higher education. due to student organizations on the UMSU campus for the formation of character which can be used as an advantage or characteristic of these students, especially towards the Faculty of Islamic Religion (FAI).